The Kingdom of God: a plan of study in three parts - Stead, F. Herbert (Bible class primers, 1893)
Contents: I. The Kingdom in Israel.- II. The Kingdom in the synoptic sayings of Jesus.- III. The Kingdom in Apostolic times.